Relationship between cultivation mode of white rot fungi and their efficiency for olive oil mill wastewaters treatment - Alaoui, Sanae Mdaghri; Merzouki, Mohamed; Penninckx, Michel J.; Benlemlih, Mohamed (Electronic Journal of Biotechnology, 2008)
Four white rot fungi (WRF) strains, Phanerochaete chrysosporium, Trametes versicolor, Coriolopsis polyzona and Pycnoporus coccineus, were tested for efficiency of treatment of Olive Oil mill wastewaters (OOMW) in relation with their cultivation mode, i.e. under the form of free mycelium, mycelium immobilized in alginate beads and solid state cultivation on Petri dishes. Study of biodegradation of phenolic compounds, chemical oxygen demand (COD) decrease and decolourisation of OOMW have shown that Coriolopsis polyzona and Pycnoporus coccineus degradation performances were apparently only slightly affected by the cell cultivation procedures experienced here. In contrast, Phanerochaete chrysosporium and Trametes versicolor showed respectively marked preferences for solid state and alginate immobilisation procedures. Both mono and polyphenolics were reduced to different extent during incubation depending on the strain, as shown by gel filtration analysis. Final pH obtained after fungal treatment of the OOMW based medium (initial pH of 5.0) was measured in order to evaluate the possibility of releasing friendly the treated wastewater in the environment. Laboratory studies as reported here may be useful for orienting the choice of a strain for treating pollution by OOMW in a particular real situation.